Land use trade-offs and synergies based on temporal and spatial patterns of ecosystem services in South China. (October 2022) - Shao, Yuting; Xiao, Yi; Sang, Weiguo
Highlights: Analysis of ESV and relationships provide new insight into land use policies. Influencing factors make obvious effects on ESV spatial distribution. Regulatory services are synergy with supply service in South China. ESVs in 2035 are increased by sustainability development scenario. Four ecological function zones contribute to the industrial configuration. Abstract: A clear understanding the relation between ecological protection and economic development provides new insight into land use policies. Land use trade-offs and synergies based on ecosystem service value (ESV) is important to regional sustainable development. In this study, we took the South China as an example, assessed the spatial and temporal changes of ecosystem service function over 20 years, and proposed a land use planning in 2035 by socio-ecological constraints and multiyear land use observations. The results showed that ESV acts a downward trend from 2000 to 2020. ESV of water conservation, soil retention, carbon sequestration, and habit quality showed a synergistic relationship with products supply. After the trade-offs and synergies of land use, the ESV in 2035 significantly improved compared with that in 2020. Finally, we proposed 4 ecological function zones land use strategy by considering trade-offs and synergies of ecological protection and economic development in studying areas to regulate the industrial configuration. This planning strategy will maintain steadily increasing of ecosystem service function until 2035, and meantime guarantee the regional ecological security.